Sociodemographic factors associated with the place of death of the Brazilian population and regional variations from 2002 to 2022 - Fernando Cesar Iwamoto Marcucci; Carla Corradi-Perini; Luis Fernando Rodrigues; Tania Pastrana (Discover Public Health)
Abstract Understanding the factors associated with the death and dying process, such as the place of occurrence and the sociodemographic influences, can support the definition of health assistance and public policies. Limited information is available for middle-income countries, like Brazil. This study identified and compared the association of sociodemographic factors (age, sex, ethnic/skin color identification, educational level and marital status) with the place of death in Brazil and its regions, in a population level research. In Brazil, death at hospital was more frequently associated with social indicators, like white people, higher educational level, more developed regions. Older age groups, male, unmarried groups and lower education level were related with higher odd to death at home, which raises concerns about unassisted or limited support in these occurrences. The debate on social demands, public policies and bioethical challenges associated with the assistance offered on death occurrences is need.